High Prevalence of Hearing Loss at the Special Olympics: Is This Representative of People with Intellectual Disability?. Issue 2 (23rd April 2013) - Hey, C.; Fessler, S.; Hafner, N.; Lange, B. P.; Euler, H. A.; Neumann, K.
<x xml:space="preserve">Abstract</x> Background The Healthy Hearing (HH) programme at the Special Olympics (SO) revealed hearing disorders in between 16 and 40% of athletes. However, it is not clear whether these prevalence represents the entire population with intellectual disability. Therefore, this study compares the hearing status of SO athletes with an intellectual disability (ID) to students with ID at a special needs school. Materials and Methods The HH screening was performed in 637 athletes (mean age 27.1 years, range 9.7–70.6 years) during the 2008 German SO Summer Games – and in 198 special needs students (mean age 12.7 years, range 6.7–20.0 years). Results Twenty‐two per cent of athletes and 18% of students failed the HH screening. Approximately 60% of the total participants received recommendations for further follow‐up and treatment without between‐group differences. Conclusions The results of the HH screening at SO events are assumed to be representative of children and adolescents with ID in special needs schools.